Sister R.S. Subbalakshmi’s Role in the Renaissance of Hindu Community : A special study based on the Educational standard of Tamil Nadu women in 19th and 20th Centuries - V, Gunapalasingam; T, Baskaran; M.S.J, Mumthaj Sameem (Indian Journal of Tamil, 2023)
The rise and fall of Hindu Community in India is a historical phenomenon. There are various personalities who dedicated themselves to the renaissance of them, regardless of victory or defeat in their efforts. Though the Hindu community seemed to advance in a number of fields in Tamil Nadu especially during the 19th and 20th centuries despite various forms of oppression and destruction. Under- age marriage was among many other factors that resulted in the backwardness of the society. In such a backdrop, the role played by a number of female personalities was immensely commendable for the reawakening activities. R.S. Subbalakshmi, Dr. Muthulatchumi Rettiyar, Sarojini Naidu, etc are a few to be added to the list of the reformers who tirelessly put all their efforts for the reawakening of Tamil women. Most notably, R.S. Subbalakshmi successfully carried out her mission towards the educational renaissance of widows. Her service has to be specially noted for her careful forward without getting caught into the clutches of the British rulers, instead obtaining their cooperation and support. She carried out her educational activities adopting the modern educational reforms of the British, while preserving the national heritage of India. The Institutions such as Saratha Ashram, Sri Saratha United Women Society, Sri Saratha Vidyalayam, which played a major role in the educational renaissance of the South Indian women, were established by her. She had to encounter untold hardships to operate those Institutions which brought a turning point in a number of educated women. Since she undertook her activities irrespective of societal differences, the rulers, philanthropists and well wishers offered their fullest support and assistance. Her activities were pioneer for the creation of other social organizations and Institutions. She is to be regarded as a forward thinker who always thought of the well being of not only the women of Tamil Nadu but of the whole South India.